On cupping and Ahmad pairs - Kalimullin, Iskander Sh. (2023)
Working toward showing the decidability of the ∀∃-theory of the Σ0 2-enumeration degrees, we prove that no so-called Ahmad pair of Σ0 2-enumeration degrees can join to 0′e.